Evidence for localized moment picture in Mn-based Heusler compounds. Issue 47 (11th November 2015) - Karel, J.; Bernardi, F.; Wang, C.; Stinshoff, R.; Born, N.-O.; Ouardi, S.; Burkhardt, U.; Fecher, G. H.; Felser, C.
Abstract : The Mn magnetic moment in positions with octahedral symmetry is localized and comprised completely by itinerant electrons. Abstract : X-ray absorption spectroscopy (XAS) and X-ray magnetic circular dichroism (XMCD) were used to probe the electronic structure and magnetic moment of Mn in Heusler compounds with different crystallographic structure. The results were compared with theoretical calculations of the magnetic and electronic properties, and it was found that in full and half Heusler alloys, Mn is metallic on both sublattices. The magnetic moment is large and localized when octahedrally coordinated by the main group element, consistent with previous theoretical work, and reduced when the main group coordination is tetrahedral. The magnetic and electronic properties of Mn in full and half Heusler compounds are strongly dependent on the structure and sublattice, a fact that can be exploited to design new materials.